Effect of amlodipine on blood glucose level in euglycemic and streptozotocin induced diabetic Albino rats and its pharmacodynamic interaction with glibenclamide - Gari, Manju; Debbarma, Rati Ranjan; Majhee, Lakhan; Choudhury, Subhankar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes is one of the largest global health emergencies of the 21st century and its co-existence with hypertension is frequent. These conditions often require polypharmacy with possible risk of drug interaction. This study is conducted to investigate the effect of amlodipine on blood glucose level in euglycemic and diabetic rats and its pharmacodynamic interaction with glibenclamide. Methods: Rats were divided into six groups of 6 rats in each group. Group 1 and 3 were non-diabetic given 1% Gum acacia and amlodipine respectively. Group 2, 4, 5 and 6 were made diabetic by using nicotinamide and streptozotocin injection intra peritoneally and given 1% Gum acacia, glibenclamide, amlodipine and amlodipine + glibenclamide respectively for the period of 28 days. Fasting Blood Glucose (FBG) levels were measured before induction of diabetes, 72 hrs after the induction, on day 0, 7th, 14th, 21st and 28th day. Results: Amlodipine produced no significant effect on FBG level in non-diabetic rats but in diabetic rats statistically significant hyperglycemia were observed on day 21st and 28th of study with the ‘p’ value (<0.05). Glibenclamide treated rats shows better controlled FBG level throughout study than concomitant administration of glibenclamide with amlodipine. Significant rise in blood FBG level with ‘P’ value (<0.05) were observed in amlodipine + glibenclamide treated group on 21st and 28th day of study. Conclusions: This study suggest amlodipine produce no effect on the FBG level of normal rats but causes significant hyperglycemia in diabetic rats. Hypoglycemic effect of glibenclamide gets blunted when co-administered with amlodipine.